Digital Gaming and Informal English Language Acquisition: Identity, Interaction, and Fluency Development among Indonesian Youth - Santosa, Rika; Pratama, Muhammad Rizky (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2025)
This study explores how international online gaming communities serve as informal spaces for English language learning among Indonesian adolescents, focusing on communicative practices, fluency development, and linguistic identity formation. The study is motivated by the limited opportunities for authentic communication in Indonesian secondary schools, where English learning remains predominantly grammar- and exam-oriented. Employing a qualitative case study design, the research involved ten high school students in Jakarta who were active members of the Airaworlf gaming community. Data were collected through participant observation during international gaming sessions, voice chat recordings, chat log analysis, and in-depth interviews exploring participants’ experiences and perceptions of language learning through gaming. Thematic analysis was applied to identify communicative patterns, linguistic strategies, and socio-technological factors influencing language acquisition. The findings reveal that online gaming fosters spontaneous, contextual, and collaborative use of English. Participants demonstrated improvements in fluency, mastery of technical vocabulary, and intercultural communicative competence. English was used not only for strategic coordination but also to build team solidarity and negotiate identities in global digital spaces. Key enabling factors include intrinsic motivation, real communicative needs, international exposure, and supportive peer environments, while challenges involve exposure to impolite language and the absence of pedagogical guidance. The study highlights international gaming communities as authentic ecosystems for informal language learning in Indonesia, revealing the emergence of hybrid linguistic identities. It contributes to applied linguistics and foreign language education, particularly within Computer-Assisted Language Learning (CALL) and digital informal learning.